Si-based thin film coating on Y-TZP: Influence of deposition parameters on adhesion of resin cement - Queiroz, José Renato Cavalcanti; Nogueira Junior, Lafayette [UNESP]; Massi, Marcos; Silva, Alecssandro de Moura [UNESP]; Bottino, Marco Antonio [UNESP]; Sobrinho, Argemiro Soares Da Silva; Özcan, Mutlu (Elsevier, 2013)
This study evaluated the influence of deposition parameters for Si-based thin films using magnetron sputtering for coating zirconia and subsequent adhesion of resin cement. Zirconia ceramic blocks were randomly divided into 8 groups and specimens were either ground finished and polished or conditioned using air-abrasion with alumina particles coated with silica. In the remaining groups, the polished specimens were coated with Si-based film coating with argon/oxygen magnetron discharge at 8:1 or 20:1 flux. In one group, Si-based film coating was performed on air-abraded surfaces. After application of bonding agent, resin cement was bonded. Profilometry, goniometry, Energy Dispersive X-ray Spectroscopy and Rutherford Backscattering Spectroscopy analysis were performed on the conditioned zirconia surfaces. Adhesion of resin cement to zirconia was tested using shear bond test and debonded surfaces were examined using Scanning Electron Microscopy. Si-based film coating applied on air-abraded rough zirconia surfaces increased the adhesion of the resin cement (22.78 ± 5.2 MPa) compared to those of other methods (0-14.62 MPa) (p = 0.05). Mixed type of failures were more frequent in Si film coated groups on either polished or air-abraded groups. Si-based thin films increased wettability compared to the control group but did not change the roughness, considering the parameters evaluated. Deposition parameters of Si-based thin film and after application of air-abrasion influenced the initial adhesion of resin cement to zirconia. © 2013 Elsevier B.V. All rights reserved.
Keywords: Adhesion; Film; Plasma; Roughness; Surface treatment; Zirconia; Alumina particles; Debonded surfaces; Deposition Parameters; Energy dispersive X ray spectroscopy; Initial adhesions; Magnetron discharges; Thin-film coatings; Zirconia ceramic; Abrasion; Alumina; Cements; Coatings; Deposition; Films; Magnetrons; Plasmas; Resins; Scanning electron microscopy; Silicon; Surface roughness; Thin films; X ray spectroscopy